2019
DOI: 10.1007/s12192-019-01018-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phosphoproteome and proteome analyses emphasize the influence of phosphorylation events during the nutritional stress of Trypanosoma cruzi: the initial moments of in vitro metacyclogenesis

Abstract: Phosphorylation is an important event in cell signaling that is modulated by kinases and phosphatases. In Trypanosoma cruzi, the etiological agent of Chagas disease, approximately 2% of the protein-coding genes encode for protein kinases. This parasite has a heteroxenic life cycle with four different development stages. In the midgut of invertebrate vector, epimastigotes differentiate into metacyclic trypomastigotes in a process known as metacyclogenesis. This process can be reproduced in vitro by submitting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Previous studies applying proteomics to investigate Chagas disease have mostly been focused on serum, looking for disease progression markers using two-dimensional gel electrophoresis prior to mass spectrometry in rats [67] and human patients [68,69]. Also, proteomic and phospho-proteomic approaches have been targeted toward the parasite itself, describing its response to nutritional stress [70] and proteins modulated during the differentiation process [71,72]. However, a large-scale, phospho-proteomic analysis of chagasic hearts, one of the most affected organs, has not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies applying proteomics to investigate Chagas disease have mostly been focused on serum, looking for disease progression markers using two-dimensional gel electrophoresis prior to mass spectrometry in rats [67] and human patients [68,69]. Also, proteomic and phospho-proteomic approaches have been targeted toward the parasite itself, describing its response to nutritional stress [70] and proteins modulated during the differentiation process [71,72]. However, a large-scale, phospho-proteomic analysis of chagasic hearts, one of the most affected organs, has not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar yields were previously reported in trypanosomatid ribosome profiling applying the same cutoff for detection (7,873 transcripts in T. cruzi [ 23 ], 7,792 [ 69 ] and 7,773 [ 70 ] transcripts in T. brucei ). Likewise, recent proteomic studies of T. cruzi detected 4,060 ( 71 ) and 4,205 ( 72 ) protein groups, while a T. brucei cell cycle study detected 4,629 protein groups ( 46 ). Therefore, the results of the two omic approaches we carried out to investigate G 1 /S cell cycle phase transition in T. cruzi are consistent with the current state of the art in trypanosomatids regarding sensitivity and coverage.…”
Section: Discussionmentioning
confidence: 94%
“…Quantitation of phosphorylated proteins in the same study showed that there are more than 7000 phosphorylation sites, of which 260 are under different regulation, including some potential drug targets, e.g., sterol biosynthesis enzymes. Next study indicated that during periods of nutritional stress, many proteins are phosphorylated, which may trigger metacyclogenesis [ 150 ]. Similarly, the proteomic comparison of the exponential phase and stationary phase of the epimastigotes quantified more than 3000 proteins [ 151 ].…”
Section: Discovery Approach—description Of the Selected Fbps And Tmentioning
confidence: 99%